2012
DOI: 10.1186/2162-3619-1-9
|View full text |Cite
|
Sign up to set email alerts
|

Ratio of involved/uninvolved immunoglobulin quantification by Hevylite™ assay: clinical and prognostic impact in multiple myeloma

Abstract: BackgroundHevyLite™ is a new, recently developed method that facilitates separate quantification of the kappa- and lambda-bounded amounts of a given immunoglobulin (Ig). Using this method, we measured intact immunoglobulin (heavy/light chain; HLC) IgG-kappa, IgG-lambda, IgA-kappa, IgA-lambda individually, as well as their deriving ratios (HLCR) in a series of IgG or IgA multiple myeloma (MM) patients, to investigate and assess the contribution of these tests to disease evaluation.Patients and methodsHevyLite™ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
42
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(48 citation statements)
references
References 17 publications
2
42
1
3
Order By: Relevance
“…Previously, we 15 and others 33 have shown a close correlation of a highly abnormal HLC ratio with short survival. In this study, we showed that this applies to patients with relapsed/refractory disease as well.…”
Section: Discussionmentioning
confidence: 54%
“…Previously, we 15 and others 33 have shown a close correlation of a highly abnormal HLC ratio with short survival. In this study, we showed that this applies to patients with relapsed/refractory disease as well.…”
Section: Discussionmentioning
confidence: 54%
“…Unlike most studies reporting abnormal HLC-r values in all MM patients [2][3]12 , this study showed the same result in the IgA-κ type of MM only; the other results were 98% for IgG-κ, 97% for IgG-λ and 92% for IgA-λ, suggesting that detection of a normal HLC-r does not rule out the diagnosis of MM in all cases 16 . Correlation analysis showed only slightly significant relationship between HLC-r (Hevylite TM ) and FLC-r (Freelite TM ) indices in the IgG MM group, both in IgG-κ and -λ isotypes, but there was no significance in the IgA group.…”
Section: Discussioncontrasting
confidence: 44%
“…In the pilot study the analysis aimed at high values of both HLC-r and FLC-r, there were correlations for both IgG and IgA types of MM (ref. 12 ). The biological variability of FLC-κ and FLC-λ demonstrates significant relationship of HLC-r index to the levels of FLC-λ, but not to FLC-κ in IgG-κ and IgG-λ types of MM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations